89 Evaluation of the strategic use of Tylan® to control liver abscess condemnation in finishing beef cattle. (7th December 2018) - Walter, L; Brown, M; Vogel, G; Hagenmaier, J; Pyatt, N; Holland, B; Word, A; Wesley, K; Defoor, P; Maxwell, C
Abstract: The objective of this study was to evaluate liver abscess prevalence in feedlot cattle fed Tylan ® for different periods. Beef steers ( n = 3, 360; initial BW = 376 ± 3.44 kg; DOF = 162 ± 1.18 d) were randomized to 1 of 6 treatments in a randomized complete block design (70 steers/pen; 8 pens/treatment). Tylan (9.7 g/ton, 100% DM basis) was included in diets during the first 42 DOF (First 42), first 84 DOF (First 84), last 84 (Last 84) DOF, first 126 (First 126) DOF, continuously (Continuous) throughout the entire feeding period, or not at all (Control). Data were analyzed using mixed model regression, with pen as the experimental unit (Stata 15; Satacorp, College Station, TX). Categorical data were analyzed using multilevel mixed-effects generalized linear model (meglm; Stata 15) with fixed effect of treatment and random effect of block. When an overall F-Test was significant ( P < 0.05), contrasts were designed to determine treatment outcomes. Days on feed, mortality, ADG, G:F, LMA, FT, marbling, and final HCW were similar among treatments ( P ≥ 0.27). Total percentage of abscessed and A+ livers decreased as days of Tylan feeding increased from the start (linear, P < 0.05). Total abscessed livers were greatest in Last 84 and Control, but least in First 126 and Continuous (16.50 or 15.69% vs. 10.36 or 10.29%, respectively; P < 0.01). Percentage of total A+ livers were greatest in Control and Last 84 while the lowest were observed in Continuous, First 84, and First 126 (8.49 or 7.36% vs. 4.96, 4.75, or 4.44%, respectively; P = 0.03). These data demonstrate that Tylan is effective at preventing liver abscesses, and provide some evidence that the time of greatest risk of liver abscess formation is early in the feeding period. Key Words: